Three-year outcomes after carotid artery revascularization: Gender-related differences. (October 2019) - Casana, Renato; Malloggi, Chiara; Tolva, Valerio Stefano; Odero Jr, Andrea; Bulbulia, Richard; Halliday, Alison; Silani, Vincenzo; Parati, Gianfranco
Objectives: Carotid artery stenosis is thought to cause up to 10% of ischemic strokes. Historically, carotid artery endarterectomy has shown a higher risk of perioperative adverse events for women. More recent trials reported conflicting results regarding the benefit of carotid artery endarterectomy and carotid artery stenting for men and women. The aim of the present retrospective study was to investigate the influence of gender on the short- (30 days) and long-term (3 years) outcomes of carotid artery endarterectomy and carotid artery stenting in a single centre. Methods: From 2010 to 2017, 912 consecutive symptomatic and asymptomatic patients who underwent carotid artery endarterectomy (389, 42.7%) or carotid artery stenting (523, 57.3%) in a single institution had been evaluated to determine the influence of sex (540 men, 59.2%, vs. 372 women, 40.8%) on the outcomes after both revascularization procedures during three years of follow-up. The primary endpoint was the incidence of death, stroke, myocardial infarction, and restenosis in the short-term follow-up. The secondary endpoint was the incidence of death, stroke, myocardial infarction, and restenosis in the long-term follow-up. Results: Mean clinical follow-up was 21.1 (16.1) months. Women had internal and common carotid artery diameters significantly smaller with respect to men. For peri-procedural outcomes, women undergoing carotid artery stenting had a higher risk of moderate (50–70%) restenosis (6 women, 2.9%, vs. 3 men, 1.0%). For long-term outcomes, women undergoing carotid artery endarterectomy had a higher rate of moderate restenosis (16 women, 16.3%, vs. 11 men, 7.6%). No significant differences in long-term outcomes were observed between men and women undergoing carotid artery stenting, even after stratification for baseline risk factors. Conclusions: Contrary to previous reports, from this single-centre study, long-term risk of events seems to be higher in women who underwent carotid artery endarterectomy than in those who underwent carotid artery stenting, while fewer differences were observed in men.